Artificial Intelligence in Oral Surgery: A Review - Dr. MD Sharifuzzaman; Dr. Vinit Kumar Singh; Dr Ankur Jain; Dr. Dhvanit Kishorbhai Dhamal; Dr. Kunal Nischal; Dr. Ranjeet Gandhi (The Bioscan, 2025)
This review examines the role of artificial intelligence (AI) in oral surgery, highlighting its applications in diagnosis, treatment planning, and predictive analytics. AI enhances precision in surgical procedures, reduces human error, and improves patient outcomes. By analyzing large datasets, AI facilitates personalized treatment strategies and offers innovative solutions to complex cases, ultimately advancing the field of oral surgery.